Concurrent AFG3L2 and SPG7 mutations associated with syndromic parkinsonism and optic atrophy with aberrant OPA1 processing and mitochondrial network fragmentation. Issue 12 (10th October 2018) - Magri, Stefania; Fracasso, Valentina; Plumari, Massimo; Alfei, Enrico; Ghezzi, Daniele; Gellera, Cinzia; Rusmini, Paola; Poletti, Angelo; Di Bella, Daniela; Elia, Antonio E.; Pantaleoni, Chiara; Taroni, Franco
Abstract: Mitochondrial dynamics and quality control are crucial for neuronal survival and their perturbation is a major cause of neurodegeneration. m ‐AAA complex is an ATP‐dependent metalloprotease located in the inner mitochondrial membrane and involved in protein quality control. Mutations in the m ‐AAA subunits AFG3L2 and paraplegin are associated with autosomal dominant spinocerebellar ataxia (SCA28) and autosomal recessive hereditary spastic paraplegia (SPG7), respectively. We report a novel m ‐AAA‐associated phenotype characterized by early‐onset optic atrophy with spastic ataxia and L‐dopa‐responsive parkinsonism. The proband carried a de novo AFG3L2 heterozygous mutation (p.R468C) along with a heterozygous maternally inherited intragenic deletion of SPG7 . Functional analysis in yeast demonstrated the pathogenic role of AFG3L2 p.R468C mutation shedding light on its pathogenic mechanism. Analysis of patient's fibroblasts showed an abnormal processing pattern of OPA1, a dynamin‐related protein essential for mitochondrial fusion and responsible for most cases of hereditary optic atrophy. Consistently, assessment of mitochondrial morphology revealed a severe fragmentation of the mitochondrial network, not observed in SCA28 and SPG7 patients' cells. This case suggests that coincidental mutations in both components of the mitochondrial m ‐AAA protease may result in a complex phenotype and reveals a crucial role for OPA1 processing in the pathogenesis of neurodegenerative disease caused by m ‐AAA defects. Abstract : m ‐AAA is a mitochondrial protease composed of AFG3L2 and SPG7/paraplegin. We report a novel m ‐AAA‐associated phenotype characterized by early‐onset optic atrophy with spastic ataxia and L‐dopa‐responsive parkinsonism. The proband carried a de novo AFG3L2 heterozygous mutation (p.R468C) along with a inherited heterozygous intragenic deletion of SPG7 . Functional analysis in yeast demonstrated the pathogenic role of AFG3L2 p.R468C mutation shedding light on its pathogenic mechanism. Analysis of patient's fibroblasts showed an abnormal processing pattern of OPA1 and severe fragmentation of the mitochondrial network.